2006
DOI: 10.1207/s15327078in0903_3
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Month‐Old Infants' Sensitivity to Social Contingency in Mother–Infant and Stranger–Infant Interaction

Abstract: Two‐month‐old infants (N = 29) participated in face‐to‐face interactions with their mothers and with strangers. The contingent responsiveness for smiles and vocalizations, while attending to the partner, was assessed for each partner in both interactions. For smiles and for vocalizations, infants were less responsive to the stranger relative to the mother when the stranger's contingent responsiveness was either more contingent or less contingent than that of the mother. Results are supportive of the hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(103 citation statements)
references
References 15 publications
(16 reference statements)
3
95
2
3
Order By: Relevance
“…The picture based on research in postindustrial societies (mainly the United States, Europe, and Japan) is as follows: newborns spontaneously orient to human faces and imitate facial expressions, for example tongue protrusion (Meltzoff and Moore 1977 ); they are also sensitive to eye contact (Farroni et al 2002 ). By two months they contingently respond to smiles and the gaze of an interlocutor (Bigelow and Rochat 2006 ;Murray and Trevarthen 1985 ). This disposition forms a basis for turn -taking: Masataka, for example, stresses the importance of sequentially dependent responding between Japanese caregivers and infants in social interaction, leading to conversational turn -taking as an early milestone, with coordination fi rst of infants ' suckling and mothers ' jiggling behavior followed by coordination of vocalization and gaze (Masataka 2003b : 44).…”
Section: Introductionmentioning
confidence: 99%
“…The picture based on research in postindustrial societies (mainly the United States, Europe, and Japan) is as follows: newborns spontaneously orient to human faces and imitate facial expressions, for example tongue protrusion (Meltzoff and Moore 1977 ); they are also sensitive to eye contact (Farroni et al 2002 ). By two months they contingently respond to smiles and the gaze of an interlocutor (Bigelow and Rochat 2006 ;Murray and Trevarthen 1985 ). This disposition forms a basis for turn -taking: Masataka, for example, stresses the importance of sequentially dependent responding between Japanese caregivers and infants in social interaction, leading to conversational turn -taking as an early milestone, with coordination fi rst of infants ' suckling and mothers ' jiggling behavior followed by coordination of vocalization and gaze (Masataka 2003b : 44).…”
Section: Introductionmentioning
confidence: 99%
“…However, the infant appears to be learning meanings about responsiveness within the experience of contingent responsiveness she receives. This was also true at 2 months of age (Bigelow & Rochat 2006), particularly in relation to infant smiling responses to adult smiles, although the patterns of similarity were more variable at 2 months than at 4 months.…”
Section: The 'Mere' Contingency Argumentmentioning
confidence: 59%
“…Bigelow (1996) showed that 3-to-5-month-olds are sensitive to socially contingent responses, prefer socially contingent strangers, associate the level of contingency with personal identities, and retain this association over time. Bigelow & Rochat (2006) later demonstrated that infants as young as 2 months engage in contingent face-to-face interactions with adults and are also sensitive to levels of social contingency. In their study infant-mother or infant-stranger dyads were brought to a laboratory space and interacted for 5 minutes.…”
Section: Early Sensitivity To Contingent Responsesmentioning
confidence: 99%
“…In most cases, the time window between infants' and adults' behaviors was chosen to be 1 second as a criterion of contingency (Bigelow, 1996;Bigelow & Rochat, 2006;Bigelow & Power, 2014;Kochanska & Aksan, 2004;Lohaus et al, 2005). In a number of experiments, the time window was longer: 2 seconds (Mcquaid et al, 2009;Bornstein et al, 2015;Gros-Louis, West, & King, 2014) or 5 seconds (Baumwell, Tamis-LeMonda, & Bornstein, 1997;45 Olson, Bates, & Bayles, 1984) following infants' actions.…”
Section: Theoretical Constructmentioning
confidence: 99%
See 1 more Smart Citation